2019
DOI: 10.1213/ane.0000000000004013
|View full text |Cite
|
Sign up to set email alerts
|

Drug Calculation Errors in Anesthesiology Residents and Faculty: An Analysis of Contributing Factors

Abstract: BACKGROUND: Limited data exist regarding computational drug error rates in anesthesia residents and faculty. We investigated the frequency and magnitude of computational errors in a sample of anesthesia residents and faculty. METHODS: With institutional review board approval from 7 academic institutions in the United States, a 15-question computational test was distributed during rounds. Error rates and the magnitude of the errors were analyzed accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Training and culture must also be considered. One study found that although both anesthesiology residents and faculty members erred frequently on a computational test, the residents committed serious errors twice as frequently as the faculty members 8 . Finally, the culture within the institution should be supportive and protective of personnel who report medication errors or near‐misses 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Training and culture must also be considered. One study found that although both anesthesiology residents and faculty members erred frequently on a computational test, the residents committed serious errors twice as frequently as the faculty members 8 . Finally, the culture within the institution should be supportive and protective of personnel who report medication errors or near‐misses 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…37 A study by Avidan and co-workers 36 also highlighted the same issue by observing the ability of anaesthetists to calculate specific drug concentrations to administer in children, finding that only 6 out of 41 (14.6%) provided the correct answers. Black and co-workers 38 concluded that inexperienced trainees made the most errors in calculations.…”
Section: Methods Types and Incidence Of Error By Typementioning
confidence: 99%
“…They may also communicate with a facility's electronic health record system. The goal of these smart pumps is to streamline pump programming and reduce errors, though the data regarding achievement of these goals are mixed [38][39][40]. Although not currently approved in the USA, target controlled infusion systems use an algorithm to account for medication accumulation and context-sensitive half time, changing the infusion rate throughout drug delivery to (ideally) maintain a constant depth of anesthesia [41].…”
Section: Infusion Pumps and Devicesmentioning
confidence: 99%